Fios que tecem o bem e o mal-estar laborais: o papel dos gestores na promoção da qualidade de vida no trabalho - Fernandes, Gilvania Morais de Araújo (2016)
The world of work has gone through varied, constant and need restructuring that meets the current modes of production, as a result, come up demanding creative workers, innovative, competent, flexible and resilient. Thus, some institutions have been concerned about the humanization of work contexts in order to mitigate the impacts of these constant restructuring and worrying about the existence of the quality of working life, which happen when the prevalence of experiences which entail welfare at work; but if overpower the discomfort at work, the employee is at risk of becoming ill. In order to disseminate the objectives and institutional goals, while preserving the humanization of workplace and worrying about the welfare of their staff, there is the manager; this, given the responsibility of their role, plays an important role in promoting quality of life at work (QLW). So, this study aimed to evaluate the relationship between managers and the promotion of quality of working life for the members of his staff, considering the views of the actors involved in the process (managers and servers under management). It is a scientific research, due to the problem of the approach is classified as qualitative; as the proposed objectives it is considered descriptive. About the collection of data and information, we used the bibliographic research, documentary and field, this latter type through a semi-structured interview, in two models and with voice recording, one for servers under management and another for managers servers. We chose for this study a non-probabilistic intentional sampling; in this order, a pilot study format, we selected to the Pro-Rector of Graduation and the Education Center of the Federal University of Rio Grande do Norte. Analysis and discussion of the results were made in light of the concept of Ergonomics Applied Activity on Quality of Life at Work, proposed by Ferreira (2012). At the end, the study showed that the major promoting factor of well-being at work is the interpersonal relationship and, in relation with the manager, the accessibility and transparency as management practices; The interviewees said there is no trouble cause at work that could promote ill-being. Furthermore, they described their labor context by working conditions, which had a median evaluation at the center and, a bad evaluation at the pro-rectory analyzed, in the work organization the well-being at work is predominant, in the recognition and professional growth the well-being has been predominant as well and, both units said that the managers have transparent practices. In addition, the interviewees from the education center as well as those from the pro-rectory of graduation said they have quality of life at work regardless of the manager being a professor or an administrative technician.So, the managers of the analyzed units have contributed for quality of life at work of their teams.